2006
DOI: 10.1038/sj.sc.3101901
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological changes in isolated spinal cord white matter in response to oxygen deprivation

Abstract: Methods: The hypoxic injury was induced by reducing the oxygen tension of the perfused solution by 80%. Compound action potentials (CAPs) were monitored before, during, and after oxygen deprivation. Results: We have found that 60 min of hypoxia reduced the conduction to 30% of preinjury level and recovered to approximately 60% of the preinjury level upon reoxygenation. Larger axons appeared to be more vulnerable to oxygen deprivation. We noted a significant decrease and recovery of the depolarizing afterpotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Measurements based on CAP area should best reflect total number of recruited fibers, a factor relevant to pathologies such as TBI, which conceivably may alter activation synchrony and conduction velocity. However, empirical results in our laboratory and others (Pryor and Shi, 2006), have indicted the use of CAP area and CAP peak to yield similar estimates of injury. In the present study, it was useful to use CAP peak to assess responses to 100 Hz stimulus trains, because baselines tended to be less stable during high frequency firing.…”
Section: Methodssupporting
confidence: 51%
See 1 more Smart Citation
“…Measurements based on CAP area should best reflect total number of recruited fibers, a factor relevant to pathologies such as TBI, which conceivably may alter activation synchrony and conduction velocity. However, empirical results in our laboratory and others (Pryor and Shi, 2006), have indicted the use of CAP area and CAP peak to yield similar estimates of injury. In the present study, it was useful to use CAP peak to assess responses to 100 Hz stimulus trains, because baselines tended to be less stable during high frequency firing.…”
Section: Methodssupporting
confidence: 51%
“…The present observation of a disproportionate CsA benefit for the myelinated axons may reflect a more severe level of mitochondrial pathology in these larger fibers. In this context, it is notable that larger diameter axons have been reported to be more susceptible to oxygen deprivation than smaller fibers, in terms of impulse conduction (Peasley and Shi, 2002; Pryor and Shi, 2006), which was attributed to a relatively greater energy demand in the larger axons. Ultrastructural observations of rat optic nerve also support a preferential vulnerability of large myelinated axons to anoxic injury, associated with mitochondrial swelling and loss of normal cristae (Waxman et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A modified sucrose gap chamber was used to assess sciatic nerve impulse conduction function 7. The endpoints of our functional assessment included compound action potentials (CAP) and latency.…”
Section: Methodsmentioning
confidence: 99%
“…After curing, fluid levels were returned to normal and electrophysiological recording reestablished. Recordings were made using a bridge amplifier (Neurodata Instruments) and data analysis performed using custom Labview software (National Instruments) on a PC as previously described 7. Instantaneous waveforms and time histories were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Both manual and mechanical cervical dislocation killing methods are designed to separate the skull from the vertebral column of the bird (ideally C0-C1 vertebral dislocation), resulting in severing of the spinal cord and/or brainstem and the main blood vessels supplying the brain (Gregory and Wotton, 1990;Parent et al, 1992;Veras et al, 2000;Cartner et al, 2007;Mason et al, 2009). It has been suggested that optimal application also produces a concussive effect on the bird due to trauma inflicted on the brainstem through the action of stretching and twisting (Harrop et al, 2001;Shi and Pryor, 2002;Pryor and Shi, 2006;Shi and Whitebone, 2006;Cartner et al, 2007;Erasmus et al, 2010a). However, both methods of cervical dislocation have been the subject of welfare concern, as research in the last 40 years has raised questions about their humaneness and consistency in poultry Wotton, 1986, 1990;Erasmus et al, 2010a), as well as other species (Tidswell et al, 1987;Cartner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%